2017
DOI: 10.1016/j.cej.2017.03.097
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Hg-contaminated marine sediments by simultaneous application of enhancing agents and microwave heating (MWH)

Abstract: This version is available at https://strathprints.strath.ac.uk/60331/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…16 Consequently, synthetic chelates, such as ethylenediamine tetraacetic acid (EDTA) and diethylene triamine pentaacetic acid (DTPA), have been used for soil remediation because of their strong chelating ability for different heavy metals. 17 However, they have poor biodegradability and are unstable at high temperatures. 18 In recent years, citric acid (CA), a tricarboxylic acid compound, has played an important role in removing heavy metals from soil via acid dissolution and chelation, 19 and is more readily biodegradable than EDTA.…”
Section: Introductionmentioning
confidence: 99%
“…16 Consequently, synthetic chelates, such as ethylenediamine tetraacetic acid (EDTA) and diethylene triamine pentaacetic acid (DTPA), have been used for soil remediation because of their strong chelating ability for different heavy metals. 17 However, they have poor biodegradability and are unstable at high temperatures. 18 In recent years, citric acid (CA), a tricarboxylic acid compound, has played an important role in removing heavy metals from soil via acid dissolution and chelation, 19 and is more readily biodegradable than EDTA.…”
Section: Introductionmentioning
confidence: 99%
“…The removal efficiency of PFOS during hydrothermal treatment is highly pH-dependent; roughly half of PFOS was removed in acidic conditions (pH = 1), but no degradation occurred in alkaline conditions (pH = 12). Post-treatment analysis showed that the carbon's properties and mass remained largely unchanged [53].…”
Section: Regeneration Of Adsorbentsmentioning
confidence: 99%
“…However, due to its quickness, selectivity, and regulated heating, microwave treatment technology is currently used to replace thermal regeneration (Falciglia et al 2018). This method entails the transformation of microwave radiation into heat at the molecular phase using adsorbent material (Falciglia et al 2017). The sorbent is uniformly heated by microwave treatment from the exterior to the interior.…”
Section: Thermal Regenerationmentioning
confidence: 99%